2014
DOI: 10.1016/j.addbeh.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

ADHD, stimulant treatment in childhood and subsequent substance abuse in adulthood — A naturalistic long-term follow-up study

Abstract: This is the longest and most complete follow-up study of children with ADHD. • 208 children with ADHD were followed until a mean age of 31 years. • Childhood ADHD increased the risk for SUD in adulthood. • Both girls and boys with ADHD were at increased risk. • Early initiation of stimulant treatment in childhood reduced the risk of later SUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
92
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 34 publications
15
92
1
5
Order By: Relevance
“…In our dataset, drug misuse was the only outcome where the increase for each ADHD symptom level in girls was significantly higher, not only in relation to less symptomatic girls, but also in comparison with increasing ADHD levels in boys. The finding of higher risk of drug misuse among girls is in line with previous follow‐up studies of clinical ADHD samples 18, 34, 80 as well as population‐based ADHD samples 21, which have shown that girls with ADHD have a higher risk for substance abuse and dependence than girls without ADHD, and also compared to boys with ADHD. The finding that childhood ADHD symptoms were associated with higher drug misuse in girls motivates particular attention and active screening routines for this group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our dataset, drug misuse was the only outcome where the increase for each ADHD symptom level in girls was significantly higher, not only in relation to less symptomatic girls, but also in comparison with increasing ADHD levels in boys. The finding of higher risk of drug misuse among girls is in line with previous follow‐up studies of clinical ADHD samples 18, 34, 80 as well as population‐based ADHD samples 21, which have shown that girls with ADHD have a higher risk for substance abuse and dependence than girls without ADHD, and also compared to boys with ADHD. The finding that childhood ADHD symptoms were associated with higher drug misuse in girls motivates particular attention and active screening routines for this group.…”
Section: Discussionsupporting
confidence: 89%
“…Prospective studies focusing on gender differences indicate that childhood ADHD may predict more steeply rising symptoms of anxiety and depression during adolescence in girls than in boys 24. Girls with ADHD also show significantly higher risks of disruptive and antisocial behaviours, as well as eating disorders (EDs) and substance dependence, as compared to girls without ADHD 18, 23, 28, 34. However, some studies have failed to show that girls with ADHD are more likely to display internalizing disorders than boys with ADHD 35.…”
Section: Introductionmentioning
confidence: 99%
“…Az ADHD szubklinikus és klinikai súlyos-ságot elérő formái egyaránt kapcsolatban állnak bizonyos internalizációs és externalizációs tünetekkel jellemezhető pszichiátriai zavarokkal [2,7]. Az ADHD-ban szenvedők között gyakori a dohányzás, az alkoholfogyasztás és a droghasználat megjelenése serdülő-és fi atal felnőtt korban [1,8,9]. Jól dokumentált jelenség, hogy az ADHD-ban szenvedő dohányosok fi atalabb korukban kezdenek el dohányozni, mint nem ADHD-s társaik, gyorsabban szoknak rá a napi szintű dohányzásra és nehezebben szoknak le róla [9].…”
unclassified
“…Ugyanez a rizikó azonban 21,5-szeres a nők, míg 4,5-szeres a férfi -ak körében. Az illegális droghasználat tekintetében a szenvedélybetegségek kialakulásának kockázata 7,7-szerese az átlagpopulációéhoz képest (a férfi aknál 5,9-szeres, míg a nőknél 38,7-szeres a normálpopulációhoz viszonyított kockázat) [8]. Az illegális szerfüggőség felnőttkorban is jelentős összefüggést mutat az ADHD-val: a magyarországi drogambulanciákon kezelt fi atal felnőtt drogfüggők 22%-ánál szűrőteszttel észlelhetőek az ADHD tünetei [13], ami összhangban áll a korábbi nemzetközi epidemiológiai kutatások által feltárt 15-25%-os aránnyal.…”
unclassified
“…Approximately 10-30% of children and adolescents with ADHD may not respond adequately to stimulants or are unable to tolerate adverse events (AEs) such as decreased appetite, mood lability, sleep disturbances, cardiovascular events, and exacerbation of comorbid psychiatric disorders (Wigal 2009;Aagaard and Hansen 2011;Clavenna and Bonati 2014;Dalsgaard et al 2014a). Additionally, stimulants have been associated with concerns regarding limited duration of action, potential for substance misuse, and patient/parental reluctance to use controlled substances (Barkley et al 1990;Hansen and Hansen 2006;Prasad and Steer 2008;Clemow and Walker 2014;Dalsgaard et al 2014b).…”
mentioning
confidence: 99%